2000
DOI: 10.1097/00002826-200003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Paradoxic Weight Gain with Selective Serotonin Reuptake Inhibitors

Abstract: It has been suggested that weight gain associated with tricyclic antidepressants (TCA) reflect actions on dopamine (DA) and histamine receptors. However, a definitive cause is purely assumptive given the nonselective pharmacology of these agents. The selective serotonin reuptake inhibitors (SSRIs), as well as agents like dexfenfluramine (DFF), have emphasized the pivotal role of serotonin (5HT) in reducing carbohydrate (CHO) intake, and have provided a more selective tool with which to study appetite regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 67 publications
1
61
0
3
Order By: Relevance
“…In fact, several studies have shown that long-term treatment with SSRIs can result in significant weight gain (e.g. Fogelson, 1991;Harvey & Bouwer, 2000). Consequently, women with PMDD may need to be cautioned about the risks of increased food cravings and food intake, particularly in combination with specific drugs or medications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have shown that long-term treatment with SSRIs can result in significant weight gain (e.g. Fogelson, 1991;Harvey & Bouwer, 2000). Consequently, women with PMDD may need to be cautioned about the risks of increased food cravings and food intake, particularly in combination with specific drugs or medications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxetine was responsible for weight gain of 3.6 % above baseline body weight. The mechanism underlying weight gain with these agents may involve several factors, primarily the remission of depression with improved appetite and carbohydrate craving due to a direct role of 5-HT on appetite regulation [71]. There is an increased risk of developing diabetes mellitus from the weight gain associated with long-term treatment with SSRIs.…”
Section: Management Of Depressionmentioning
confidence: 99%
“…Antidepressants have been associated with weight gain to varying degrees. For the selective serotonin reuptake inhibitor (SSRI) class of antidepressants (fluoxetine, sertraline, paroxetine, and citalopram), this may reflect their multiple serotonergic activities, 31 one of which is an affinity for serotonin (5-hydroxytryptamine 2C [5-HT 2C ]) receptors. Recent research has implicated these receptors as having a role in the regulation of appetite.…”
Section: Treatments For Psychiatric Disorders Exacerbate Metabolic Symentioning
confidence: 99%